Contribution of a groundwater-influenced hinterland drainage system to the restoration of salmonid spawning grounds at the upper river Danube - Pander, Joachim; Casas-Mulet, Roser; Geist, Juergen (Frontiers in Environmental Science, 2023)
Groundwater-influenced ditches, so called hinterland drainage systems (HDS), accompany many heavily modified water bodies (HMWBs). Herein, we evaluate the usefulness of including HDS as functional habitats in river restoration approaches by assessing their role as salmonid recruitment areas in HMWBs. We tested the functionality of spawning grounds in a groundwater-influenced HDS compared to the quality of those not influenced by groundwater (OHB 1 and OHB 2), based on bioindication using brown trout eggs. Eggs were placed in each compartment of a two-layered container of 20 cm diameter and 30 cm total depth (known as the HydroEcoSedimentary Tool) pre-filled with sediment, mimicking hyporheic conditions. A total of 81 HESTs were evenly distributed across the three sites to assess egg and larvae mortality whilst exposed at two substrate depths (5 -10 cm and 17 - 22 cm). In addition, key physico-chemical variables such as dissolved oxygen, temperature, pH, turbidity, electric conductance and substratum composition were analyzed. Mean egg mortality in the HDS was 33% lower than in both non-groundwater-influenced spawning grounds, whereas mean larval mortality was highest in the HDS (95%) compared to 74 % at OHB 1 and 66% at OHB 2. The exposure depth of eggs had a significant influence on mortality, with more dead eggs and larvae in the deeper substrate layers, most likely attributed to an increase of fine sediment and a decrease of oxygen availability over time. Particularly the HDS revealed high mortality rates of larvae since it had a 17% lower mean oxygen level compared to the other spawning grounds. These findings suggest that if additional measures such as substratum restoration were undertaken to increase oxygen availability within HDS, these groundwater-dominated ditches could be incorporated as part of an efficient river restoration strategy.